The Role of Islamic Religious Education Teachers in Fostering Students’ Noble Character in the Era of Communication Technology Development - Heri Mahmudianto; Ridho Riyanto (Golden Ratio of Data in Summary, 2026)
The development of communication technology has had a significant impact on students’ behavior and character. This study aims to analyze the role of Islamic Religious Education (PAI) teachers in fostering students’ noble character at Madrasah Ibtidaiyah PP Al-Ihslah Saren Bandar. The research employs a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The findings reveal that PAI teachers play a central role in fostering noble character through the implementation of adaptive learning methods aligned with technological advancements, providing behavioral role models, and integrating moral values into daily learning activities. This study emphasizes the importance of teachers’ roles as moral guides in the digital era, enabling students to internalize moral values despite exposure to modern communication technologies.